GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2017)
A dataset containing 5142 species occurrences available in GBIF matching the query: TaxonKey: Natalus stramineus Gray, 1838. The dataset includes 5142 records from 96 constituent datasets: 1 records from Tejidos de quirópteros de tres localidades del caribe colombiano. 2 records from Ghent University - Zoology Museum - Vertebrate collection. 2 records from SUI Vertebrate Collection. 1 records from ISM Mammalogy Collection. 1 records from UConn Mammals. 154 records from MVZ Mammal Collection (Arctos). 31 records from Biodiversidad mastozoológica del Eje Volcánico Transversal. 947 records from KUBI Mammalogy Collection. 4 records from MBML-Mamiferos - Coleção de Mamíferos. 2 records from MLZ Mammal Collection (Arctos). 4 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 5 records from Biología del murciélago mastín enano (Eumops bonariensis nanus) en Yucatán. 204 records from Base de datos de mamíferos de México depositados en colecciones de Estados Unidos y Canadá. 7 records from University of Florida Vertebrate Paleontology. 6 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 18 records from CUMV Mammal Collection (Arctos). 4 records from Peces y Mamíferos de la región de Norogachi, Alta Sierra Tarahumara, Chihuahua. 5 records from The mammals collection (ZM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1 records from Museum Victoria provider for OZCAM. 2 records from CRCM Vertebrate Collection. 2 records from Vertebrados terrestres de San Juan de Camarones, Durango. 3 records from Museu Paraense Emilio Goeldi - Mastozoology Collection. 183 records from Field Museum of Natural History (Zoology) Mammal Collection. 15 records from Museum of Comparative Zoology, Harvard University. 2 records from iNaturalist Research-grade Observations. 3 records from Colección Nacional de Mastozoología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 24 records from Actualización de la base de datos de la Colección de mamíferos del Museo de Zoología 'Alfonso L. Herrera'. 25 records from Mammals housed at MHNG, Geneva. 1 records from Caracterización biológica del Monumento Natural Yaxchilán como un elemento fundamental para el diseño de su plan rector de manejo. 17 records from Actualización de la base de datos de la Colección Regional Durango (Mammalia). 1 records from HSU Vertebrate Museum Mammals Collection. 7 records from CAS Mammalogy (MAM). 7 records from UMMZ Mammal Collection. 1 records from SBMNH Vertebrate Zoology. 150 records from LACM Vertebrate Collection. 9 records from Mamíferos de Nuevo León, México (UANL). 31 records from Colección de Mamíferos de la Sierra Volcánica Transversal de México (UAM-I). 2 records from SysTax - Zoological Collections. 36 records from Natural History Museum (London) Collection Specimens. 4 records from Macaulay Library Audio and Video Collection. 170 records from Computarización de la Colección Nacional de mamíferos del Instituto de Biología, UNAM. 2 records from Distribución geográfica de las aves y los mamíferos de las zonas montanas de los estados de San Luis Potosí e Hidalgo circundantes de la Sierra Gorda. 46 records from Computarización de las colecciones de vertebrados terrestres de la Escuela Nacional de Ciencias Biológicas, IPN Fase 1: Estado de México, Hidalgo, San Luis Potosí y Tlaxcala. 17 records from Computarización de la Colección Regional Durango (Mammalia). 162 records from Computarización de las colecciones de vertebrados terrestres de la Escuela Nacional de Ciencias Biológicas, IPN - Fases 2 y 3. 10 records from Anfibios, reptiles y mamíferos del corredor biológico del norte de Yucatán depositados en las colecciones de la Escuela Nacional de Ciencias Biológicas. 2 records from Deforestación y fragmentación del hábitat: consecuencias ecológicas sobre la fauna de mamíferos de la selva tropical estacional. 18 records from Sistematización de las colecciones científicas del Instituto de Historia Natural y Ecología, (IHNE) Chiapas. 146 records from Computarización de las colecciones de vertebrados terrestres de la Escuela Nacional de Ciencias Biológicas, IPN - Fases 2 y 3. 2 records from Vertebrados terrestres del Corredor Biológico Sierra Madre del Sur, Chiapas, México. 2 records from Actualización de la base de datos de la colección mastozoológica de El Colegio de la Frontera Sur, San Cristóbal de las Casas. 40 records from Uso y monitoreo de los recursos naturales en el Corredor Biológico Mesoamericano (áreas focales Xpujil-Zoh Laguna y Carrillo Puerto). 30 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 72 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 46 records from Inventario de los mamíferos de las reservas de la biósfera Mapimí, La Michilía, El Cielo y Calakmul. 81 records from Actualización de la base de datos del Atlas Mastozoológico de México. 366 records from NMNH Extant Specimen and Observation Records. 11 records from Biodiversidad de los mamíferos en el Estado de Michoacán. 19 records from UWBM Mammalogy Collection. 1 records from LSUMZ Mammals Collection. 39 records from Mammals Specimens. 11 records from FHSM Mammals Collection. 270 records from CNMA/Colección Nacional de mamíferos. 186 records from TTU Mammals Collection. 31 records from Colección de Mamíferos de la Sierra Volcánica Transversal de México (UAM-I). 7 records from Estacion Biologica Donana - CSIC, Mammal Collection. 18 records from UCLA Donald R. Dickey Bird and Mammal Collection. 248 records from Actualización de la base de datos del estado de Morelos de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 15 records from WNMU Mammal Collection (Arctos). 1 records from UCM Mammal Collection (Arctos). 40 records from Colección de Mamíferos del Museo de Zoología 'Alfonso L . Herrera', México (MZFC, UNAM). 61 records from PSM Vertebrates Collection. 9 records from Mamíferos de Nuevo León: distribución y taxonomía. 279 records from UAZ Mammals. 80 records from Collection Mammalia SMF. 9 records from CNMA/Colección de Mamíferos de la Estación de Biología Chamela. 198 records from AMNH Mammal Collections. 5 records from La mastofauna del cuaternario tardío de México. 1 records from Registros de quirópteros de tres localidades del caribe colombiano. 1 records from Bosque Mesófilo de Montaña de México. 11 records from Geographically tagged INSDC sequences. 103 records from MSB Mammal Collection (Arctos). 195 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 13 records from Mamíferos del Estado de Veracruz. 1 records from UTEP Mammals (Arctos). 53 records from Mammalogy Collection - Royal Ontario Museum. 9 records from Diversidad y distribución mastofaunística en las regiones prioritarias para la conservación del estado de Oaxaca. 2 records from Australian Museum provider for OZCAM. 2 records from Formación de las colecciones de referencia de aves y mamíferos de la Reserva de la Biosfera de Sian Ka'an, Quintana Roo, México. 3 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Mammalogy National Collection (MACNMa).. 10 records from Colección nacional de zoología. 2 records from Palaeobiology - Vertebrate Comparative Osteology Collection - Royal Ontario Museum. 12 records from Catálogo de los mamíferos de México en resguardo de The Natural History Museum (London), Inglaterra. 26 records from Mamíferos silvestres de la cuenca del río Mezquital-San Pedro, Durango-Nayarit. 15 records from Angelo State Natural History Collections (ASNHC) - Mammalogy Collection. 9 records from USAC Mammals Collection. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences